Lodgepole Pine Bole Wood Density and Decay Rate 1, 11, and 22 Years After Felling in Central Montana, United States - Lutes, Duncan C.; Hardy, Colin C. (Frontiers in Forests and Global Change, 2021)
Estimates of large dead and down woody material biomass are needed for ecological applications, such as nutrient cycling, wildlife habitat assessment and fire effects, and for climate change science (carbon). Many methods are used to assess the volume of woody material: however, estimates of wood density are required to convert volume to biomass. To assess initial wood density and decomposition rate, this study examined in situ wood density of lodgepole pine logs at the Tenderfoot Creek Experimental Forest, central Montana, USA, 1, 11 and 22 years after felling. Mean wood density decreased from 0.39 g cm-3 to 0.27 g cm-3 over 22 years and the single exponential decay rate was k = 0.012 yr-1 1 and 11-years post-felling and 0.022 yr-1 11 and 22 years post-felling. A common 5-category decay classiﬁcation system was evaluated for estimating wood density by decay class, which identified significant difference in three of four observed classes.